Effectiveness of a Fall Prevention Preparation Program on Caregivers’ Knowledge and Preparedness, and Balance in Older Adults Living in the Community - Chutimarat, Ananya; Konkam, Busakorn (Ramathibodi Medical Journal, 2025)
Background: Falls among the elderly are a major concern in aging societies, impacting the physical, mental, social, and economic well-being of older adults and their families. Fall prevention is crucial and requires family involvement. Objectives: To assess the effectiveness of the fall prevention preparation program on caregivers’ knowledge and preparedness, as well as on the balance of older adults. Methods: Quasi-experimental research was conducted among 64 pairs of caregivers and older adults aged 60 and above who were at risk of falls. Participants were divided into an intervention group (32 pairs) and a control group (32 pairs) using purposive sampling. Data collection included personal information questionnaires, caregivers’ knowledge and fall prevention preparedness questionnaires, and elderly balance assessment using the Five Times Sit to Stand Test. Data were analyzed using descriptive statistics and t test. Results: Caregivers in the intervention group showed significant improvements in knowledge and fall prevention preparedness scores postprogram (P < .001) and had higher scores compared to the control group (P < .001) . The balance of older adults also significantly improved after the program (P < .001). Conclusions: The fall prevention preparation program effectively enhanced caregivers’ knowledge, leading to better fall prevention preparedness and improved balance in older adults.